Knowledge of Breast Cancer and Breast Self-Examination Behavior of Older Women Living at Municipal Area in Ubon Ratchathani Province - Chabuakam , Natthaya; Phisaiphanth, Suparat (Medical Journal of Sakon Nakhon Hospital, 2024)
Older women are at greater risk of breast cancer than other age groups. Regular breast self-examination (BSE) is crucial for early detection of breast abnormalities. This study aimed to 1) study the knowledge of breast cancer in older women 2) explore BSE behavior of older women, and 3) determine the relationship between knowledge of breast cancer and BSE behavior among older women. This research was a cross-sectional correlational study conducted between October 2020 and January 2021. A simple random sampling was used to select 152 older women. Data were collected using the demographic questionnaire, the knowledge of breast cancer questionnaire, and the BSE behavior questionnaire. The reliability the knowledge of breast cancer and the BSE behavior questionnaire were 0.79 and 0.82, respectively. Data were analyzed using the descriptive statistics and Spearman's rank correlation coefficient. The results showed that the level of knowledge of breast cancer was poor ( = 11.80, S.D. = 4.07), and the level of BSE behavior was low ( = 10.32, S.D. = 9.20). Moreover, the relationship between the knowledge of breast cancer and the BSE behavior among older women was statistically significant (rs = .389, p < .001). This study recommends creating proper interventions to improve the knowledge of breast cancer and promote regular and correct BSE among older women.